Conceptualising bullying in an Aboriginal context as reported by the Yamaji community, to inform the development of a bullying prevention program that is culturally sensitive to the needs of Aboriginal students - Coffin, Juli (2010)
The Solid Kids Solid Schools project aimed to capture the unheard voices of Aboriginal children and community members on the issues surrounding ‘bullying’. In an Aboriginal context bullying is different and the outcomes are different, yet mainstream programs are utilized to combat the issue. We need to know how bullying is different for Aboriginal children and young people, why it is different and what does this difference mean in terms of addressing this issue in a school and community setting? A community based steering group guided the direction of this study and the larger Solid Kids Solid Schools project. Snowball sampling and volunteer recruitment (Sarantakos 1993) were used to secure consent and interviews with over 190 Aboriginal respondents in the Yamaji (Midwest) region of Western Australia. Respondents included children, youth, Elders and parent/caregivers. Face to face interviews were conducted and transcribed by Aboriginal researchers to ensure cultural validity. Interviews were used to understand Aboriginal respondents’ experiences with bullying, its effects and what was needed to reduce its prevalence and harm to those who are targeted. While bullying was found to be an issue for all children, bullying perpetration and victimisation among Aboriginal children and youth appears to be different. Further, Aboriginal children and youth seem to be affected differently to non-Aboriginal children and youth. Bullying is not thought to be cultural or acceptable and the long term effects were not widely recognised among community members. Bullying appears to have a pattern of acceptance among young people and intra-racial bullying was found to be the most hurtful to Aboriginal children and youth. Long-term violence and community acceptance of bullying allows other anti-social behaviours to manifest and the belief in the need for young people to ‘fight all the way up’ is expected by the community. Intra-racial bullying and other forms of aggression need to be dealt with by both the school and the wider community setting and recognized as a serious issue facing many Aboriginal children and families. Without fully understanding this very personal, emotive and critical issue in an Aboriginal context we cannot take action to reduce its negative impact. This shared understanding must be developed with sensitivity whilst maintaining cultural integrity for Aboriginal people. While the effects of bullying are widely known for mainstream children and communities, this study provides the first major insight into how this harmful behaviour is perceived and experienced by Aboriginal people. Only with this understanding can we begin to develop community-based interventions to help young people to deal with this problem behaviour